Rumah Belajar Ceria: Tutoring in Mathematics and English for Elementary School Students in Tenrigangkae Village - Lhenny Ardillah Latif; Muhammad Ammar Naufal; Hamzah Upu; Wahidah Sanusi; Zaid Zainal (Journal of Community Services and Development, 2025)
The Rumah Belajar Ceria program was implemented as part of the community service component of the KKN-PPL program of Universitas Negeri Makassar in Tenrigangkae Village, aiming to enhance elementary school students’ motivation and understanding of Mathematics and English. This initiative was driven by limited learning facilities and a lack of academic support outside school hours, causing children to spend more time playing without academic guidance. The program was conducted informally in three phases: planning, implementation, and evaluation. The learning strategy emphasized interactive, contextual, and game-based approaches. The results showed increased motivation, participation, and confidence among students, along with significant improvement in understanding basic concepts. In addition, the program received positive support from parents and the community, strengthening social bonds between students, parents, and university students. These findings highlight that informal game-based learning models can serve as an alternative solution to improve both educational quality and community empowerment in rural areas.